CUSTARD (Cranfield University Space Technology Advanced Research Demonstrator) - A Micro-System Technology Demonstrator Nanosatellite. Summary of the Group Design Project MSc in Astronautics and Space Engineering. 1999-2000, Cranfield University - Hobbs, Stephen; Turner, Ray (Cranfield University, 2003)
CUSTARD (Cranfield University Space Technology And Research Demonstrator) was the group design project for students of the MSc in Astronautics and Space Engineering for the Academic Year 1999/2000 at Cranfield University. The project involved the initial design of a nanosatellite to be used as a technology demonstrator for microsystem technology (MST) in space. The students worked together as one group (organised into several subgroups, e.g. system, mechanical), with each student responsible for a set of work packages. The nanosatellite designed had a mass of 4 kg, lifetime of 3 months in low Earth orbit, coarse 3-axis attitude control (no orbit control), and was capable of carrying up to 1 kg of payload. The electrical power available was 18 W (peak). Assuming a single X-band ground station at RAL (UK), a data rate of up to 1 M bit s-1 for about 3000 s per day is possible. The payloads proposed are a microgravity laboratory and a formation flying experiment. The report summarises the results of the project and includes executive summaries from all team members. Further information and summaries of the full reports are available from the College of Aeronautics, Cranfield University.
Keywords: Nanosatellite; Space technology; Group Design project